Analisis Risiko Produksi Pupuk Phonska di PT Petrokimia Gresik Jawa Timur - Sitinjak, Dewi Elisabeth; Prasetyo, Edy; Setiyawan, Hery (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Phonska fertilizer production at PT Petrokimia Gresik has fluctuated and often failed to meet production targets. This study aims to analyze priority risk sources and analyze effective mitigation strategies to address production risks at PT Petrokimia Gresik. The research location was determined purposively, considering that it is an agro-industrial company with high production capacity. The research was conducted in October-November 2025. The method used in this study was the case study research method. The key persons in this study were determined using the purposive method, and they were production staff. Data collection techniques included observation and interviews. The analysis in this study was conducted using the Coefficient of Variation and HoR (House of Risk) methods. The results of the study indicate a medium level of risk with a CV value of 9%. In addition, the results of HoR phase 1 obtained 22 risk events and 25 risk sources. Fourteen risk sources were identified as priority risks that require the design of a risk management strategy. The results in HoR 2 show 10 management strategies that can be implemented by the company in handling priority risk sources. The risk management strategies are based on the highest to lowest ETD values in sequence, namely cross-checking mechanisms, production rescheduling, team coordination, incoming raw material control, technical skills training, replacement of damaged machine parts, safety stock planning, preventive maintenance, temperature monitoring, and the use of magnetic separators.